2013
DOI: 10.1136/bjophthalmol-2012-303051
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between floppy eyelid syndrome and obstructive sleep apnoea

Abstract: OSA might be an independent risk factor for eyelid hyperlaxity and severe OSA is common in patients with FES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 24 publications
3
49
1
2
Order By: Relevance
“…Some investigations [4,7], show that severe OSAS is common in patients with FES and significantly relates with, suggesting OSAS might be an independent risk factor both for FES and eyelid hyperlaxity. Wang et al [6] in a recent meta-analysis confirmed that FES is very common in OSAS, but it is not within the general non-OSAS population; FES risk is 4.12 times higher in OSAS than in non-OSAS individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations [4,7], show that severe OSAS is common in patients with FES and significantly relates with, suggesting OSAS might be an independent risk factor both for FES and eyelid hyperlaxity. Wang et al [6] in a recent meta-analysis confirmed that FES is very common in OSAS, but it is not within the general non-OSAS population; FES risk is 4.12 times higher in OSAS than in non-OSAS individuals.…”
Section: Discussionmentioning
confidence: 99%
“…15 A more recent prospective study evaluated 114 patients consecutively admitted for a sleep study and found that 14 (16%) had hyperlaxity of both lower and upper eyelids with papillary conjunctivitis, while 54 (60%) had hyperlaxity alone. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Muniesa TUAS olmayan grupta bu oran %8 olarak saptanmış, fakat aradaki fark istatistiksel olarak anlamlı bulunmamıştır. 22 Elli dört TUAS hastasını değerlendirdiğimiz çalışmada; McNab ve ark. ile Muniesa ve ark.nın serilerine benzer olarak hastalara %13 (7/54) oranında GGS'nin eşlik ettiği saptanmışdır.…”
Section: Discussionunclassified
“…çalışmalarında 89 TUAS hastasından 54 (%60,67) 'ünde kapak laksitesinde artma tespit ederlerken, hasta olmayan grupta bu oran %32 (8/25) olarak saptanmış ve aradaki fark istatistiksel olarak anlamlı bulunmuştur. 22 Bizim çalışmamızda, grup 1'deki hastaların %19'unda (4/21), grup 2'deki hastaların %39,4 (13/33)'ünde, tüm hastaların ise %31,5 (17/54) 'inde göz kapağı hiperlaksitesi saptanmıştır. Göz kapağı hiperlaksitesi grup 2'de grup 1'e kıyasla iki kat fazla görülmesine rağmen aradaki fark istatistiksel olarak anlamlı bulunmamıştır.…”
unclassified